Spillover, efficiency and equity effects of regional firm subsidies - Sebastian Siegloch; Nils Wehrhöfer; Tobias Etzel (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We analyze the effects of a large place-based policy, subsidizing up to 50% of the investment costs of manufacturing firms in East Germany. We show that a one-percentage-point decrease in the subsidy rate leads to a 1% decrease in manufacturing employment. We document important local spillovers for untreated construction and retail sectors, counties connected via trade, and local tax rates. There is no evidence for regional reallocation or changes in commuting and residential decisions. The cost per job amount to at most 23000. Last, we show that local subsidies are substantially more effective in curbing regional inequality than place-blind policies.
Keywords: H24; J21; J23; 330; place-based policies; employment; spillovers; administrative microdata